2014
DOI: 10.1200/jco.2014.55.1572
|View full text |Cite
|
Sign up to set email alerts
|

Margins for Breast-Conserving Surgery With Whole-Breast Irradiation in Stage I and II Invasive Breast Cancer: American Society of Clinical Oncology Endorsement of the Society of Surgical Oncology/American Society for Radiation Oncology Consensus Guideline

Abstract: The ASCO review panel endorses the SSO/ASTRO recommendations with qualifications, as follows. The panel reinforces and amplifies the guideline authors' call for the monitoring of outcomes of the guideline at the institutional level, as institutions transition to adopting the SSO/ASTRO recommendations; would place greater emphasis on the importance of postlumpectomy mammography for cases involving microcalcifications; and calls for flexibility in the application of the guideline in light of the generally weak e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 3 publications
2
119
1
2
Order By: Relevance
“…Ataseven and colleagues22 reported that neoadjuvant chemotherapy‐induced pathological complete cancer response rates increased the surgical options for BCS without compromising clinical outcomes, an approach requiring future investigation. Future TM approaches for treating MIBC should recommend standardized operating procedures, involving tumour bed clips to facilitate image‐guided RT63, 64, 65, 66, 67, 68, 69. A minority of studies (8 of 24) in the present review referred to tumour bed boost RT following BCS for MIBC.…”
Section: Discussionmentioning
confidence: 98%
“…Ataseven and colleagues22 reported that neoadjuvant chemotherapy‐induced pathological complete cancer response rates increased the surgical options for BCS without compromising clinical outcomes, an approach requiring future investigation. Future TM approaches for treating MIBC should recommend standardized operating procedures, involving tumour bed clips to facilitate image‐guided RT63, 64, 65, 66, 67, 68, 69. A minority of studies (8 of 24) in the present review referred to tumour bed boost RT following BCS for MIBC.…”
Section: Discussionmentioning
confidence: 98%
“…According to this guideline, the use of no ink on tumor (ie, no cancer cells adjacent to any inked edge/surface of specimen) as the standard for an adequate margin in invasive cancer in the era of multidisciplinary therapy is associated with low rates of ipsilateral breast tumor recurrence and has the potential to decrease re-excision rates, improve cosmetic outcomes, and decrease health care costs (6).…”
Section: Breast Conservation Therapy and "Oncoplastic" Surgerymentioning
confidence: 99%
“…If positive marginal oncogenic cellswere found, the patients were subjected to additional surgery, hyperactive anxiety and discomfort [2][3][4][5]. There for it is becoming an indispensable need to analysis oncogenes in molecular labels by incorporating cancer specific biomarkers to improve cancer identification and screening.…”
Section: Introductionmentioning
confidence: 99%